Development of antioxidant-rich edible film using eggshell and tapioca flours with kelakai (Stenochlaena palustris) extract - Yulia Nurul Ma'rifah; Mariatul Adawiyah; Sigit Ariwibowo; Iryanti Fatyasari Nata; Rinna Juwita; Duc-Thang Vo (Konversi, 2025)
One of the major challenges in the food industry in the limited shelflife products. A promising approach to address this issue is the use of edible films-thin, consumable layers that protect food from environmental factors such as moisture, oxygen, and humidity. This study aimed to evaluate edible films based on varying ratios of chicken eggshell flour and tapioca flour, determine the optimum concentration of Kelakai (Stenochlaena palustris) extract as an antioxidant source, and assess the films’ physical, chemical, and application properties. Edible films were prepared using eggshell flour (0-30% w/w), tapioca flour (5 g), distilled water (93.5 mL), Kelakai extract (0-10% v/v), and glycerol (1.5 g). The mixture was heated to ±96°C at 1000 rpm for 40 minutes, cast into 20 × 10 cm molds, and dried at 50°C for 24 hours. The best formulation—10% eggshell flour with 5% Kelakai extract—produced a film with 0.174 mm thickness, 1.5 MPa tensile strength, 27.4% elongation, and water vapor transmission rate of 10.0278 g/m²·h. FT-IR analysis revealed C-H, O-H, and C=O functional groups. Antioxidant activity showed 5.19% scavenging activity after 10 minutes. The film successfully preserved sausage for 7 days, demonstrating its potential to extend shelf life and serve as an eco-friendly packaging alternative.